La tecnología y su incidencia en la interacción entre docentes y estudiantes de primero de bachillerato de la Unidad Educativa 24 de Mayo - Intriago Cedeño, Nubis Eneida (2023)
This paper explores the relevance of Information and Communication Technologies (ICT) in the educational field and its influence on the learning process. It is emphasized that transformative success in education is closely related to the use of these technologies and the reflective and critical attitude of educators when incorporating them. ICT, such as mobile devices, the Internet, computers, email and video games, enable the transmission, processing and dissemination of information and communication. It is emphasized that virtual environments intended for teaching and learning can have diverse impacts on students, depending on variables such as discipline, effort, pedagogical strategies and interaction between teachers and students. The relevance of ICT in the collaborative learning process is also highlighted, by facilitating the creation of virtual environments, research and evaluation of the knowledge acquired. The study was carried out in a specific educational institution, with the purpose of demonstrating that the interaction between teachers and students, supported by ICT and the virtual environment, leads to an improvement in learning. The research was characterized by being both qualitative and quantitative, and included data collection through surveys directed at second-year high school students and teachers. The structure of the text is divided into several chapters, which cover the description of the topic of study, the theoretical framework, the methodology used in the research and the results obtained. These results in turn led to the formulation of general and specific recommendations regarding teaching and learning strategies. In summary, the text emphasizes the importance of ICT and the interaction between teachers and students in contemporary education.